Pencil Beam Planar Ka-Band Antenna Array Using Waveguide Displaced Radiators Sections for Millimeter Wave Applications - Hany S. Hussein; Mohamed Ismeil; M. S. Yasseen; Yuri E. Sedelnikov; Mohamed N. Shaaban (IEEE Access)
This study presents the design and analysis of a wideband planar Ka-band antenna array for millimeter-wave 5G wireless systems, radar, and satellite communication systems. The proposed antenna array utilizes waveguide sections with radiating elements (grooves) positioned on the outer side and a feeder at a specific distance from the planar input surface. The radiating elements in each waveguide section are symmetrically at a distance from the planar input surface, determined mathematically to ensure in-phase excitation. The design simplifies construction by eliminating the need for a separate mirror component, thereby increasing the gain coefficient by reducing shading and scattering effects. The methodology involves arranging waveguide sections in a single plane, with radiating elements positioned to create an excitation field with specific amplitude and phase distributions. The theoretical framework is based on using waveguide structures with periodically placed irregularities to produce a pencil beam radiation pattern. The proposed antenna has been carefully studied using CST microwave studio software. Key results of the proposed design include a main lobe directivity of 29.9 dBi, a side lobe level (SSL) of -14.8 dB, width of radiation pattern of 3.6° at 37.5 GHz, and an impedance bandwidth of $S_{11} \lt -10$ dB from 28 to 34.4 GHz and 34.9 to 37.9 GHz, validating the antenna’s effectiveness.